Case Reports: STAIR for Strengthening Social Support and Relationships Among Veterans With Military Sexual Trauma and PTSD. Issue 2 (1st February 2016) - Cloitre, Marylene; Jackson, Christie; Schmidt, Janet A.
ABSTRACT: Military sexual trauma (MST) is associated with high rates of post-traumatic stress disorder (PTSD) and multiple comorbid symptoms. In addition, women Veterans with MST report negative perceptions of social support, poor relationships, and difficulties in social and role functioning. Treatments for PTSD do not provide interventions to improve social or relationship functioning and do not consistently produce positive benefits regarding these outcomes. This article presents a series of case studies in which an intervention focused on building social support and relationship skills is delivered to Veterans with PTSD and MST. The intervention, Skills Training in Affective and Interpersonal Regulation (STAIR) promotes social engagement and skills that support greater role functioning. It can be used as a stand-alone treatment, as an adjunctive intervention to PTSD therapies or as part of a combination therapy in which skills precede trauma-focused work (STAIR Narrative Therapy). Further investigation is suggested to determine the added benefits of incorporating skills building to PTSD or other diagnosis-specific interventions.